2009
DOI: 10.1186/1477-7819-7-83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) assessment for Her-2 status in breast cancer

Abstract: Background: The concordance rate between IHC and FISH according to clinical performance is still controversial. We report a prospective study to reflect the concordance between IHC and FISH in Guilin city, People's Republic of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…A few of studies [11,[17][18][19] show a concordance rate between IHC 3+ and discordance rate between IHC 2+ with FISH. But, other studies [14,20] show a concordance rate between IHC 2+ and FISH. Therefore, agreement between IHC and FISH are still controversial, in our concordance in the cases of IHC 3+ is similar with theirs, but there are some differences in the cases of IHC 2+.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A few of studies [11,[17][18][19] show a concordance rate between IHC 3+ and discordance rate between IHC 2+ with FISH. But, other studies [14,20] show a concordance rate between IHC 2+ and FISH. Therefore, agreement between IHC and FISH are still controversial, in our concordance in the cases of IHC 3+ is similar with theirs, but there are some differences in the cases of IHC 2+.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, agreement between IHC and FISH are still controversial, in our concordance in the cases of IHC 3+ is similar with theirs, but there are some differences in the cases of IHC 2+. This may due to the different sensitivity and specificity of the antibodies and probe used in this study, [14] or because of subjective interpretative variation in reporting, variable pre-analytical conditions, imperfect IHC methodology [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene amplification could be demonstrated only in some of the samples that are found 2+ by IHC (Yeh). Studies have reported that FISH positivity in IHC 2+ samples varies between 7% and 89% (Ciampa et al, 2006;Rossi et al, 2006;Kuo et al, 2007;Sui et al, 2009;Goud et al, 2012;Zhang et al, 2012). Such diverse results might be due to the differences in the number of patients included in studies, centers' and/or pathologists' experience, and the test kits used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity and specificity of the assay vary significantly depending on commercial antibody used. By contrast, FISH method is more standardized and less variable and has, therefore, emerged as a ''gold standard'' for assessment of HER2 status [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%